Changing characteristics of statin-related cIMT trials from 1988 to 2006. (March 2016) - Davidson, Michael H.; Tomassini, Joanne E.; Jensen, Erin; Neff, David; Polis, Adam B.; Tershakovec, Andrew M.
Abstract: Objectives: Changes in cIMT have not been consistently correlated with cardiovascular risk reduction in clinical studies. The variability of carotid intima media thickness (cIMT) changes in published statin LDL-C-lowering studies in relation to various baseline and study characteristics was assessed. Methods: This was an exploratory analysis of study-level data pooled from statin-treatment arms of 13 studies conducted during 1988–2006. Baseline mean common carotid artery (CCA)/cIMT, maximum mean CCA/cIMT and LDL-C levels, and annualized cIMT changes were estimated for the overall studies, those conducted before/after 2000, and in risk-based subgroups. Potential relationships between prespecified covariates and cIMT changes were assessed. Results: Baseline mean CCA/cIMT and LDL-C levels were higher in the combined studies conducted before year 2000 (0.8521 mm) than after 2000 (0.7458 mm), and somewhat higher in study populations of patients with coronary heart disease risk and those with greater LDL-C reductions. Mean CCA/cIMT changes were also larger for the studies conducted before 2000 (−0.0119 mm/year) than after 2000 (−0.0013 mm/year). Notably, studies conducted before 2000 were of longer duration (≥2 years) than after 2000 (<2 years). Heterogeneity in cIMT change was attributed to baseline and study-design characteristics. Longer study duration and greater LDL-C reductions were significantly related to larger annualized cIMT changes. Maximum cIMT results were similar. Conclusion: Baseline cIMT and LDL-C levels were lower, and cIMT changes were smaller in statin cIMT trials conducted after 2000 than those before 2000. These trends are consistent with increased treatment and control of high LDL-C levels over recent years in clinical practice, and may influence the results of cIMT studies. Highlights: Factors related to variability of cIMT changes in statin trials over time were assessed. Studies before 2000 had higher baseline cIMT and LDL-C, and larger cIMT changes than after 2000. Study timing and duration, and LDL-C reduction were related to heterogeneity in cIMT changes. These trends are consistent with increased treatment/control of LDL-C levels in recent years. Such factors should be considered when designing future cIMT lipid-lowering trials.